Functional characteristics of a cloned epithelial Na+/H+ exchanger (NHE3): resistance to amiloride and inhibition by protein kinase C. - Tse, C M (1993)
We previously cloned an isoform Na+/H+ exchanger (NHE3), which was expressed only in intestine, kidney, and stomach. We show here the functional characteristics of NHE3 as a Na+/H+ exchanger by stably transfecting NHE3 cDNA into PS120 cells, a fibroblast cell line that lacks endogenous Na+/H+ exchangers. NHE3 was 39- and 160-fold more resistant to inhibition by amiloride and ethylisopropyl amiloride, respectively, than NHE1, the housekeeping Na+/H+ exchanger isoform. Although both exchangers were stimulated by serum, NHE3 was inhibited by phorbol 12-myristate 13-acetate (PMA), which stimulated NHE1. Mechanistically, serum and PMA stimulated NHE1 by an increase in the apparent affinity of the exchanger for intracellular H+. In contrast, serum stimulated and PMA inhibited NHE3 by a Vmax change. When NHE3 was stably expressed in Caco-2 cells, an intestinal epithelial cell line, NHE3 was functionally expressed in the apical membrane. Thus, NHE3 is a good candidate to be an epithelial brush border Na+/H+ exchanger. Furthermore, Na+/H+ exchangers can be rapidly regulated by mechanisms that change either the Vmax or the affinity for intracellular H+, depending on the Na+/H+ exchanger subtype.